PELANGGARAN PRINSIP ITIKAD BAIK DALAM PERJANJIAN ASURANSI PADA P.T. ASURANSI JIWASRAYA CABANG PADANG - Masri, Esther (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2018)
This study uses empirical juridical method where research with a view to legal provisions in practice. This study concerns the basic factors underlying the onset of any breach of the principle of utmost good faith in the insurance agreement as well as how the settlement and legal consequences of the breach of the principle of utmost good faith in the contract of insurance. The author uses the qualitative data analysis to make an assessment of data that authors get on the field with the help of literatures related research. Based on the research that earned the author the P.T. Asuransi Jiwasraya (Persero) Padang Branch that the factors underlying the violation of the principle of utmost good faith can be caused by internal factors (the insurer) is an insurance agent and risk selectors (underwriter) and external factors i.e. insured parties. Violation of the dishonest agents caused the insurer gives a description of the products offered to the prospective insured because only the pursuit of targets and commissions, vice versa the insured provides false information when responding to a question from the insurer. Completion of the offence principle of utmost good faith this is done first by deliberation, if agreement was not reached will proceed through court proceedings. As a result of legal violations of principle of utmost good faith is the insurance agreement void or in other words the insurer has no duty to indemnify if the claims of the insured object.